Airport delay prediction model based on regional residual and LSTM network - Jingyi QU; Meng YE; Xing QU (Tongxin xuebao)
Nowadays,the civil aviation industry has a high precision requirement of airport delay prediction,so an airport delay prediction model based on the RR-LSTM network was proposed.Firstly,the airport information,meteorological information and related flight information were integrated.Then,the RR-LSTM network was used to extract the features of the fused airport data set.Finally,the Softmax classifier was adopted to classify and predict the airport delay.The proposed RR-LSTM network model can not only extract the time correlation of airport delay data effectively,but also avoid the gradient disappearance problem of deep LSTM network.The experimental results indicate that the RR-LSTM network model has a prediction accuracy of 95.52%,which achieves better prediction results than the traditional network model.The prediction accuracy can be improved about 11% by fusing the weather information and the flight information of the airport.